From Colorings to Weavings - Miro, Eden Delight (Archīum Ateneo, 2014)
We present a methodology for constructing weavings from 2-colorings of the plane. In particular, we consider tilings T of the plane by triangles and their corresponding triangle groups G. We derive 2-colorings of T using the index 2 subgroups of G.